The Dual Role of an Air Distribution System, Both Reducing the Concentration of Infectious Agents and Spreading Infectious Agents - Sandberg, Mats (Frontiers in Built Environment, 2022)
A large number of people becoming sick due to COVID -19 pandemic are infected in their homes. Therefore, the spread of infectious agents, when infectious and susceptible individuals stay together in their homes, is an important issue. Usually, ventilation is regarded as a process of only diluting and removing contaminants, but it is also a mechanism for spreading contaminants. The latter issue is of major importance when there is a pandemic. An air distribution system must therefore be viewed from a wider perspective than is generally the case. There is a need of a shift of paradigm. The scope of this paper is to introduce new concepts that will make it possible to analyse air distribution systems from such a wider perspective.